2019
DOI: 10.3390/molecules24203770
|View full text |Cite|
|
Sign up to set email alerts
|

In Vitro Antimicrobial Activities of Organic Acids and Their Derivatives on Several Species of Gram-Negative and Gram-Positive Bacteria

Abstract: The objective of this study was to determine the in vitro antimicrobial activity of several organic acids and their derivatives against Gram-positive (G+) and Gram-negative (G−) bacteria. Butyric acid, valeric acid, monopropionin, monobutyrin, monovalerin, monolaurin, sodium formate, and ProPhorce—a mixture of sodium formate and formic acid (40:60 w/v)—were tested at 8 to 16 concentrations from 10 to 50,000 mg/L. The tested bacteria included G− bacteria (Escherichia coli, Salmonella enterica Typhimurium, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 56 publications
5
60
0
1
Order By: Relevance
“…Several studies showed similar observations: the study of the silver nanoparticles loaded by extracts from Allophylus serratus leaf [18] or by Tectona grandis seeds extract [19]. [11]. The second-highest relative intensity was that the 1,3-benzodioxol-4-ol, a phenolic benzothiazole derivative, which approved various b ological importance because of its anticancer, antimicrobial, and antioxidant activiti [12].…”
Section: The Biogenic Properties Of a Factorovskyi Silver Nanoparticmentioning
confidence: 79%
“…Several studies showed similar observations: the study of the silver nanoparticles loaded by extracts from Allophylus serratus leaf [18] or by Tectona grandis seeds extract [19]. [11]. The second-highest relative intensity was that the 1,3-benzodioxol-4-ol, a phenolic benzothiazole derivative, which approved various b ological importance because of its anticancer, antimicrobial, and antioxidant activiti [12].…”
Section: The Biogenic Properties Of a Factorovskyi Silver Nanoparticmentioning
confidence: 79%
“…are mainly susceptible to MCFA, while Gram-negative bacteria (i.e., Escherichia coli, Campylobacter jejuni, Salmonella spp.) are more sensitive to SCFA [27,28]. This can be explained by the lipophilic nature of MCFA that allows them to have a stronger antibacterial activity mainly against Gram-positive species, whereas the presence of lipopolysaccharide (LPS) in the Gram-negative cell wall confers resistance to these species [29].…”
Section: Antimicrobial Properties Of Organic Acidsmentioning
confidence: 99%
“…While the majority of the research on formic acid as an antimicrobial in food animal production has focused on foodborne Salmonella spp., there have been some studies with other pathogens inhabiting the GIT. As indicated by the in vitro work of Kovanda et al (68), formic acid may be effective against other GIT foodborne pathogens as well, including E. coli and Campylobacter jejuni. Early research indicated that organic acids, such as lactic acid and commercial blends that contained formic acids as one of several components, could lower Campylobacter levels in poultry (135,138).…”
Section: Impact On Foodborne Pathogens In the Gastrointestinal Tractmentioning
confidence: 98%
“…The chemical form of formate the bacteria are exposed to appears to matter as well. Kovanda et al ( 68 ) screened several Gram-negative and Gram-positive microorganisms and compared Minimum Inhibitory Concentration (MIC) responses on sodium formate (500–25, 000 mg/L) and a blend of sodium formate and free formate (40/60 w/v; 10–10,000 mg/L). Based on the MIC estimates, they found that sodium formate was only inhibitory to strains of Campylobacter jejuni, Clostridium perfringens, Streptococcus suis , and Streptococcus pneumoniae , but not E. coli, Salmonella Typhimurium, or Enterococcus faecalis .…”
Section: Antimicrobial Mechanisms Of Formic Acidmentioning
confidence: 99%